2015
DOI: 10.1002/adfm.201500176
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Robust Organic Counterion‐Induced Vesicles: Reversible Thermal Behavior for Optical Temperature Sensor and Synergistic Catalyst upon Removal of Amine

Abstract: A general concept of organic counterion‐directed molecular strategy for thepreparation of robust vesicles is developed. Functional amphiphilic ammonium salts (L1‐L3) bearing readily available oligo‐ethyleneglycol‐based ligand 1 and single‐tailed fatty amines self‐assemble into vesicles with controllable sizes in aqueous media. The organic counterion‐induced vesicles (OCIVs) are characterized by dynamic light scattering, transmission electron microscopy, and acid triggered release of hydrophilic drug (DOX·HCl).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…The macrocyclic polyamine was selected to form SA with lipoic acid considering mainly its adjustable nitrogen atoms, which facilitate the optimization of the areas between hydrophobic and hydrophilic parts of the resulting SA to achieve the construction of expected nanovesicles. [6a,b] As shown in Figure a–c, the transmission electron microscopy (TEM) and dynamic light scattering (DLS) measurements exhibited that the SA‐bearing different macrocyclic polyamines can all self‐assemble into spherical nanoparticles above their critical aggregation concentrations (CACs; Figure S1, Supporting Information). However, the well‐established Phloxine B leakage assay indicated that only SA‐bearing macrocyclic polyamines with three and four nitrogen atoms self‐assembled into lipoic acid vesicles (LAVs), while the sample with two nitrogen atoms gave rise to a micelle‐like structure (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The macrocyclic polyamine was selected to form SA with lipoic acid considering mainly its adjustable nitrogen atoms, which facilitate the optimization of the areas between hydrophobic and hydrophilic parts of the resulting SA to achieve the construction of expected nanovesicles. [6a,b] As shown in Figure a–c, the transmission electron microscopy (TEM) and dynamic light scattering (DLS) measurements exhibited that the SA‐bearing different macrocyclic polyamines can all self‐assemble into spherical nanoparticles above their critical aggregation concentrations (CACs; Figure S1, Supporting Information). However, the well‐established Phloxine B leakage assay indicated that only SA‐bearing macrocyclic polyamines with three and four nitrogen atoms self‐assembled into lipoic acid vesicles (LAVs), while the sample with two nitrogen atoms gave rise to a micelle‐like structure (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the cross‐linked lipoic acid vesicles was exemplified with the vesicles constructed by the SA containing three nitrogen atoms (Scheme 7), and the synthetic details could be found in the “Experimental Section.” The 1 H NMR measurement verified the successful preparation of the cLAVs with the broadened proton signals after ring‐opening disulfide exchange polymerization (Figure S3a,b, Supporting Information) and the disappeared macrocyclic polyamine signals after removal of polyamine (Figure S3c, Supporting Information). The gel permeation chromatography (GPC) analysis demonstrated that the number‐average molecular weight of cLAVs reached up to 26 370 g mol −1 (Figure S4, Supporting Information), over 120 times higher than that of LA (M.W.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations